Oncogenic transformation by the human polyomaviruses - Imperiale, Michael J (Oncogene, 2001)
The human polyomaviruses, BKV and JCV, were first isolated 30 years ago, BKV from the urine of a renal transplant patient (Gardner et al., 1971) and JCV from the brain of a patient with progressive multifocal leukoencephalopathy (PML) (Padgett et al., 1971), a neurodegenerative disease in which glial cells, the cells that produce myelin, are destroyed. These viruses share much in common with their well-studied simian cousin, SV40, but each also has its own unique features that distinguish it from the monkey virus. In this review, I will provide a brief overview of the biology of the two human viruses, an analysis of their transforming potential and their oncoproteins, the T antigens, and a discussion of the possible role of these viruses in human cancer.